The Credibility of Preachers in the Young Preachers Assembly Institution in Guiding Community Worship in the Rilau Ale District of Bulukumba Regency - Muh. Ikram; Muliaty Amin; St. Nasriah (Jurnal Mercusuar, 2023)
This research aims to identify the credibility of dai in community worship development in the Rilau Ale District, Bulukumba Regency. The credibility of dai is measured based on competence, attitude, personality, and dynamic nature in delivering dakwah (religious preaching). Data is obtained through interviews with dai, members of the majelis taklim (Islamic study group), and village heads who collaborate with the Majelis Dai Muda (MDM) of Bulukumba Regency. Data analysis is conducted using qualitative and thematic approaches. The research findings indicate that dai in the MDM of Bulukumba Regency have good credibility in community worship development. Dai’s competence, supported by a high level of education and mastery of the teachings of the al-Qur’an and as-Sunnah, instills trust in the community to participate in the development programs. Additionally, dai’s wise, friendly, gentle, and polite attitudes make dakwah easier to accept and internalize by the community. During the development process, dai from MDM exhibit good attitudes and personalities, including dealing with differences in understanding within the community. They do not impose their will and always convey dakwah messages in a wise and thoughtful manner. The dynamic nature of dai in dakwah is also evident from their ability to adapt materials and methods to the level of community understanding. The community’s perception of the credibility of dai from MDM in Bulukumba Regency is highly positive. Dai’s credibility makes the community feel comfortable and interested in participating in the worship development programs. Dai is regarded as a public figure that enlightens and helps build awareness among the community to better comprehend and practice religious teachings in their daily lives. In conclusion, this research emphasizes the significant influence of dai’s credibility from MDM in the worship development of the community. Competence, attitude, personality, and dynamic nature of dai are crucial factors in building awareness and fostering positive change within the community, aligning with religious teachings. Therefore, the credibility of dai plays a vital role as an agent of formation and positive transformation in the community.